Verbal Soccer Strategy in Fiqh Learning to Improve Student Motivation in Madrasah - Putri, Mella Ika; Sabri, Ahmad; Batubara, Juliana (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
Fiqh learning in Islamic schools still faces the problem of low student motivation and participation due to the dominance of lecture methods that create a monotonous learning atmosphere. This study aims to describe the application of the Verbal Football strategy in Fiqh learning and analyze its contribution to increasing student learning motivation. The study used a descriptive qualitative approach with observation, interview, and documentation techniques with Fiqh teachers and eighth-grade students of Madrasah Al Falah Padang. The results showed that the application of the Verbal Football strategy packaged in the form of learning tools and student worksheets was able to create an interactive learning atmosphere through an educational game format resembling a soccer match, so that students were more active in discussions, involved in group work, motivated to compete healthily, and showed improvements in cognitive, affective, and psychomotor aspects. Thus, the Verbal Football strategy can be an alternative innovation in Fiqh learning that is effective in increasing student learning motivation in Islamic schools and is relevant to be applied in the broader context of religious education.